2013
DOI: 10.1016/j.expneurol.2013.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Environmental enrichment promotes robust functional and histological benefits in female rats after controlled cortical impact injury

Abstract: Environmental enrichment (EE) consistently induces marked benefits in male rats after traumatic brain injury (TBI), but whether similar efficacy extends to females is not well established. Hence, the aim of this study was to reassess the effect of EE on functional and histological outcome in female rats after brain trauma. Twenty-four normal cycling adult female rats underwent verification of estrous stage prior to controlled cortical impact (CCI) or sham injury and then were assigned to EE or standard (STD) h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
58
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 70 publications
(62 citation statements)
references
References 56 publications
(138 reference statements)
2
58
1
1
Order By: Relevance
“…[18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33]36 EE alone, however, did not lead to an increase in memory retention, which is in contrast to that seen in adult models. 23,26,29,33 As reported for Experiment 1, the buspirone (0.1 mg/kg) STD-housed group was also significantly better than the STD vehicle group in the MWM. The data also showed that the combination group (buspirone, 0.1 mg/ kg + EE) performed markedly better than the single therapy groups (i.e., EE plus vehicle and STD buspirone) in both the acquisition of spatial learning and memory retention, which suggests an additive effect.…”
Section: Discussioncontrasting
confidence: 64%
See 3 more Smart Citations
“…[18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33]36 EE alone, however, did not lead to an increase in memory retention, which is in contrast to that seen in adult models. 23,26,29,33 As reported for Experiment 1, the buspirone (0.1 mg/kg) STD-housed group was also significantly better than the STD vehicle group in the MWM. The data also showed that the combination group (buspirone, 0.1 mg/ kg + EE) performed markedly better than the single therapy groups (i.e., EE plus vehicle and STD buspirone) in both the acquisition of spatial learning and memory retention, which suggests an additive effect.…”
Section: Discussioncontrasting
confidence: 64%
“…[18][19][20][21][22][23][24][25][26] Likewise, EE has also been shown to confer neurobehavioral and histological benefits in adult male rats after CCI 20,23,[26][27][28][29][30][31][32][33][34] and fluid percussion brain injury. [35][36][37][38][39][40] Recently, the benefits of EE have also been extended to female rats after CCI.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Rats were trained prior to TBI or sham surgery to perform the task without error (i.e., traverse the beam under 5 s). Task of BW was assessed before trauma, and on D0, D1 and D2 post-TBI that consisted of three trials for any time evaluated [30]. Data for each time were the mean of three trials.…”
Section: Evaluation Of Vestibulomotor Functionmentioning
confidence: 99%